Utilizing Superpave Gradations to Assess Permanent Deformation and Fracture in HMA Mixes - Muhammad Haris Javed; Inam Ur Rehman; Murad Khan; Akhtar Abbas; Adnan Khan (Journal of ICT, Design, Engineering and Technological Science, 2022)
This research study investigates the Fatigue Failure & Permanent Deformation response behaviour of four (04) HMA mixtures. The selected gradations have a Nominal Maximum Aggregate Size (NMAS) of 19.0 mm, and the gradation blends passed Above (ARZ), Below (BRZ), and Through (TRZ), the restricted zone. Along with the Superpave ARZ, BRZ & TRZ conventional NHA, “Class A” gradation was also checked for performance parameters, thus producing results in contrast to the conventional NHA gradation already used by highway industries Pakistan. Three (03) performance tests were carried out in this study that, includes Indirect Tensile Strength Test (IDT), the repeated Indirect Tensile Fatigue Test (ITFT), and the Moisture Susceptibility Test. Statistical analysis was also done based on laboratory-produced results. Two-Level Factorial Design was also carried out using the statistical tool Minitab-16. Statistical analysis shows that OBC, P0.075/Pbe (Dust to Binder Ratio), and the Peak Force significantly affect No of Cycles to Fatigue Failure. A linear Model was developed with an R square of .74 which seems to fit well. IDT Test evaluated the TRZ mix as having the best laboratory fracture resistance properties of all tested mixes, while ARZ performed best in the Moisture Susceptibility test. Moreover, this study gave us insight into Superpave IDT as a practical and reliable way to measure all the parameters needed in the HMA Fracture Mechanics method.